Shining castles and humans of metal/floral appearance – metaphorical language in the Palaiologan romances Kallimachos and Velthandros - Fonseca, Rui Carlos (2020)
About eight centuries after Heliodorus, the Greek novel resurfaced in the twelfth century, in Komnenian Byzantium, and again two centuries later under the Palaiologan dynasty. This latter literary revival was due to the political stability of the imperial Byzantine government, which promoted cultural production, rhetorical education, and patronage networks. Kallimachos and Velthandros, two Palaiologan romances presented as court literature, combine ancient and medieval tropes with rhetorical artistry to blur the boundaries between the artificial and the natural. Castles and objects made of precious metals thus resemble living, natural spaces, and human characters are portrayed in metallurgical, anthomorphic, and zoomorphic terms.